Vibrations induced by railway traffic in buildings: Experimental validation of a sub-structuring methodology based on 2.5D FEM-MFS and 3D FEM. (1st August 2021) - Colaço, Aires; Alves Costa, Pedro; Amado-Mendes, Paulo; Calçada, Rui
Highlights: Global methodology for the assessment of ground-borne vibrations. Hybrid model based on FEM-MFS approach for modelling the track-ground system. 3D FEM approach for modelling the building (take into account SSI effects). Full characterized experimental test site, comprising track, ground and structure. Experimental validation of the global sub-structuring methodology. Abstract: The assessment of vibrations induced by railway traffic is a complex issue that demands numerical tools for prediction of its generation and propagation along the track-ground-building system. For that purpose, this paper presents a 2.5D FEM-MFS model for modelling the track-ground system, where the Finite Element Method (FEM) is used to model the complex geometries of the track and the Method of Fundamental Solutions (MFS) to model the infinite ground. The main feature of this methodology is its ability to deal with any generic track-ground cross-section and soil properties in an efficient way, allowing modelling large domains with a reasonable computational cost. In the same numerical tool, a 3D FEM model is used for modelling the building, with the soil-structure interaction being considered in a simplified way. An experimental case study is presented and explored, allowing the experimental validation of the proposed methodology and stressing the potentialities of the model on the study of vibration propagation problems induced by railway traffic.